An Ordinance Relating to Offenses and Disorderly Conduct and Repealing Ordinances no. 152, 178, & 471, Olympia City Council, Ordinance no. 523, § 3 (Washington, 1891). - (:unkn) unknown (My University, 1891)
That any person who shall draw, exhibit or attempt to use any pistol, dirk, dagger, slung-shot, cross-knuckles or knuckles of brass, lead or other metal, or other deadly or dangerous weapon, upon, to or against any person or persons in said city of Olympia, shall upon conviction thereof before a police justice of said city, be fined in any sum not less than twenty-five nor more than one hundred dollars, and in default of the payment thereof, shall be committed to the city Jail until such fine and costs are paid, not to exceed sixty days.
Keywords: BRANDISHING